ANALISIS KEADILAN DALAM PEMIDANAAN TERHADAP IKUT SERTA MELAKUKAN PENGANIAYAAN BERAT DENGAN RENCANA - Celine Florentza Simanungkalit; R Rahaditya (Jurnal Hukum Adigama, 2021)
The crime of premeditated severe maltreatment is an act of persecuting another person, or severe persecution and carried out with a prior plan, can be punished with imprisonment for a maximum of twelve years, but if the act causes the person being persecuted to lose his life (experiencing death), shall be sentenced to a maximum imprisonment of fifteen years. In the process of a criminal act of serious maltreatment with a plan, it can be carried out with the participation or of a person, it is both physically and psychologically. And in the process of punishing the perpetrators, mistakes often occur in determining the class of the perpetrators which results in the achievement of a justice which is one of the objectives of the law itself in the judicial process. To achieve justice that is appropriate and based on law, proper and good thinking framework is needed by law enforcement officers in the judicial process, as well as improvement of positive law so that the basis used in deciding a case is appropriate and fair.